PERSPEKTIF SISWA KELAS TINGGI MI TERHADAP REWARD AND PUNISHMENT DALAM PEMBELAJARAN - Pratiwi, Nadilla; Herianingtyas, Nur Luthfi Rizqa (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
The background of this research is my curiosity, which wants to measure whether the school applies rewards and punishments in learning. This study aims to analyze how the perspective of high school students for giving rewards and punishments carried out by their teachers when the learning process is in progress. Besides that, I also want to know what the teacher's behavior is like when teaching when learning takes place in the application of reward and punishment in grades 4, 5 and 6. This research activity was conducted in the form of observational, interviews and questionnaires. The material used in this study is qualitative data, namely data obtained from the results of observation data, interviews and questionnaires. This research was only conducted by 1 respondent, namely students in grades 4, 5 and 6. It was found that the application of reward and punishment in learning was going well and in accordance with standards like giving gifts and punishments in the Pakansari Bogor waterfall. From this we can concluded that various perspectives of high-level students towards giving rewards and punishments in this learning are in line with expectations